Prosaic sites of multiculturalism as educational encounters in neo-liberal higher education: Sociological imagination and reflexive teaching and learning in the multicultural classroom. (November 2018) - Peyrefitte, Magali
The article reflects on the pedagogy of a first-year sociology and criminology module that was developed around the idea of 'Researching the City' in order to introduce students to the methodological and analytical processes of doing research in social science. Part of the assessment strategy centres around a weekly online diary which enables students to use positionality by way of reflecting on their experience of the city, of London, most specifically, due to the location of the university and the origin of the students. Expanding on Ash Amin's idea of 'prosaic sites of multiculturalism', the article argues in favour of the transformative potential of a pedagogy that value experiential knowledge and is responsive to this form of knowledge in providing the theoretical and methodological tools to make sense of personal experiences in relation to structures and structural constraints. In this, the pedagogy works to develop a sociological imagination as a pedagogical route to empowering students in and out of the classroom in opposition to a neo-liberal ethos that instead values individualisation and competitiveness and is at present transforming higher education and society as a whole in the United Kingdom.